1978
DOI: 10.1113/jphysiol.1978.sp012142
|View full text |Cite
|
Sign up to set email alerts
|

Voltage sensitive calcium channels in the presynaptic terminals of a decrementally conducting photoreceptor

Abstract: 5. The action potential is followed by a large undershoot which can last several seconds. The amplitude and duration of the action potential and the duration of the undershoot all grow in increasing concentrations of TEA up to 400 mm, the highest concentration tested. The threshold for the action potential decreases as the concentration of TEA is increased to 10 mM; increasing the concentration further has no effect on the threshold. These observations suggest that TEA blocks a voltagesensitive potassium condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
6
45
0
Order By: Relevance
“…The barnacle photoreceptor neurone does not ordinarily display a regenerative response upon depolarization. Ca action potentials, however, can be elicited from the terminal region by depolarization with light or current in the presence of TEA or 3-AP (Ross & Stuart, 1978). These compounds presumably block a K current that normally counters inward current flowing through voltage-sensitive Ca channels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The barnacle photoreceptor neurone does not ordinarily display a regenerative response upon depolarization. Ca action potentials, however, can be elicited from the terminal region by depolarization with light or current in the presence of TEA or 3-AP (Ross & Stuart, 1978). These compounds presumably block a K current that normally counters inward current flowing through voltage-sensitive Ca channels.…”
Section: Resultsmentioning
confidence: 99%
“…We define the 'somatic region' as the perikaryon, its dendritic processes, and the axon hillock (the first 1 mm of axon); following the D. R. EDGINGTON AND A. E. STUART convention of Ross & Stuart (1978), the final 1 mm of axon, axon branches within the commissure of the supraoesophageal ganglion, and the presynaptic terminal arborizations, are referred to as the 'terminal region'.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This large size enabled stable intra-cellular recordings (Gwilliam, 1963(Gwilliam, , 1965Brown, Hagiwara, Koike & Meech, 1970; , as well as intra-axonal recordings (Shaw, 1972; Ozawa, Hagiwara, Nicolaysen & Stuart, 1976;Hudspeth, Poo & Stuart, 1977; Hudspeth Ross & Stuart, 1978). These studies have revealed that illumination causes a slow, sustained depolarization but no spike 0022-3751/80/1090-0414 $07.50 © 1980 The Physiological Society H. KOIKE AND K. TSUDA potentials in the photoreceptor cell and its axon, and that this depolarizing receptor potential spreads electrotonically towards the axon terminal which is several millimetres away from the cell body (Shaw, 1972;.…”
Section: Introductionmentioning
confidence: 99%